Seasonal changes in amino acids, protein and total nitrogen in needles of fertilized Scots pine trees - Näsholm, T.; Ericsson, A. (Tree Physiology, 1990)
Seasonal changes in amino acids, protein and total nitrogen in needles of 30-year-old, fertilized Scots pine ( Pinus sylvestris L.) trees growing in Northern Sweden were investigated over two years in field experiments. The studied plots had been fertilized annually for 17 years with (i) a high level of N, (ii) a medium level of N, or (iii) a medium level of N, P and K. Trees growing on unfertilized plots served as controls. In control trees, glutamine, glutamic acid, γ-aminobutyric acid, aspartic acid and proline represented 50–70% of the total free amino acids determined. Arginine was present only in low concentrations in control trees throughout the year, but it was usually the most abundant amino acid in fertilized trees. Glutamine concentrations were high during the spring and summer in both years of study, whereas proline concentrations were high in the spring but otherwise low throughout the year. In the first year of study, glutamic acid concentrations were high during the spring and summer, whereas γ-aminobutyric acid was present in high concentrations during the winter months. This pattern was less pronounced in the second year of investigation. The concentrations of most amino acids, except glutamic acid, increased in response to fertilization. Nitrogen fertilization increased the foliar concentration of arginine from < 1 μmol g dw −1 in control trees to a maximum of 110 μmol g dw −1. Trees fertilized with nitrogen, phosphorus and potassium had significantly lower arginine concentrations than trees fertilized with the same amount of nitrogen only. Protein concentrations were similar in all fertilized trees but higher than those in control trees. For all treatments, protein concentrations were high in winter and at a minimum in early spring. In summer, the protein concentration remained almost constant except for a temporary decrease which coincided with the expansion of new shoots. Apart from arginine, the amino acid composition of proteins was similar in all treatments.